Germline Non-CDKN2A Variants in Melanoma and Associated Hereditary Cancer Syndromes - Chiara Anna Fiasconaro; Alice Carbone; Silvia Giordano; Francesco Cavallo; Paolo Fava; Barbara Pasini; Yuliya Yakymiv; Sara Marchisio; Pietro Quaglino; Simone Ribero; Gabriele Roccuzzo (Diseases)
The etiology of melanoma is multifactorial and arises from the interplay of genetic, phenotypic, and environmental factors. The genetic predisposition to melanoma is influenced by a complex interaction among genes exhibiting varying levels of penetrance (high, moderate, and low), each contributing differently to the susceptibility of the disease. Furthermore, penetrance may vary based on the incidence of melanoma across diverse populations and geographical regions. Advances in genetic sequencing technologies have facilitated the identification of novel genes potentially associated with melanoma, as well as the characterization of relevant germline variants. While the most extensively researched variant is CDKN2A, recent studies have highlighted other variants unrelated to CDKN2A as significant areas of investigation. Among them, high-penetrance genes encompass CDK4, BAP1, POT1, TERT, ACD, and TERF2IP. In contrast, moderate-penetrance genes include MC1R, MITF, and SLC45A2, while low-penetrance genes consist of OCA2, TYRP1, and TYR. In addition to elevating the risk of melanoma, these genetic alterations may also predispose individuals to internal neoplasms. This review aims to provide a comprehensive overview of the definitions of sporadic, multiple primary, familial, and hereditary melanoma, with a particular emphasis on non-CDKN2A germline variants and their dermoscopic and phenotypic features.